PERANCANGAN APLIKASI PENAWARAN JASA LAUNDRYBERBASIS ANDROID (STUDI KASUS: UMKM WILAYAH JAKARTA TIMUR) - Widhu Pralakso, - (2018)
Micro, small and medium enterprises (UMKM) engaged in the laundry services currently has evolved quite significantly, especially in residential areas. This laundry services SMALL MEDIUM ENTERPRISES development need to be supported to enhance a better economy anymore, so is expected to spur SMALL MEDIUM ENTERPRISES-SMALL MEDIUM ENTERPRISES more. This research aims to design and build applications offer android-based laundry services using RAD (Rapid Application Develop), whereas for the design of the application, the researchers used the studio and android application SQL applications. Laundry service offerings applications is expected to assist the parties use it, because the application has features that are easy to use by either the consumer or the provider of the kind of SMALL MEDIUM ENTERPRISES in the field of laundry services